2020
DOI: 10.1016/j.ebiom.2020.102779
|View full text |Cite|
|
Sign up to set email alerts
|

Dolutegravir plus lamivudine for maintenance of HIV viral suppression in adults with and without historical resistance to lamivudine: 48-week results of a non-randomized, pilot clinical trial (ART-PRO)

Abstract: Background: We investigated the efficacy of a switch to dolutegravir plus lamivudine in aviremic individuals without evidence of persistent lamivudine resistance-associated mutations in baseline proviral DNA population sequencing. Methods: Open-label, single-arm, 48-week pilot trial. HIV-1 infected adults, naïve to integrase inhibitors, with CD4+ above 350 cell/mL and fewer than 50 HIV-1 RNA copies per mL the year prior to study entry switched to dolutegravir plus lamivudine. Participants were excluded if base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…In one of these studies, the risk was limited to patients with a shorter virological suppression time before the switch (<96 months), albeit at the limit of statistical significance [ 75 ]. All other real-life data available today, however, agree in terms of the exclusion of an association between the M184V mutations in historical GRTs and VF to DTG/3TC, at least up to 48- or 96-weeks after switch [ 23 , 74 , 75 , 77 , 80 , 92 , 94 , 95 , 96 ], and regardless of the duration of the time-lapse between the detection of RAMs and the start of 2DR [ 23 ].…”
Section: Assessment Of Pre-existing or Archived Resistancementioning
confidence: 96%
See 3 more Smart Citations
“…In one of these studies, the risk was limited to patients with a shorter virological suppression time before the switch (<96 months), albeit at the limit of statistical significance [ 75 ]. All other real-life data available today, however, agree in terms of the exclusion of an association between the M184V mutations in historical GRTs and VF to DTG/3TC, at least up to 48- or 96-weeks after switch [ 23 , 74 , 75 , 77 , 80 , 92 , 94 , 95 , 96 ], and regardless of the duration of the time-lapse between the detection of RAMs and the start of 2DR [ 23 ].…”
Section: Assessment Of Pre-existing or Archived Resistancementioning
confidence: 96%
“…A recent meta-analysis reported random-effects pooled estimates for a viral suppression of 98.6% and 97.5% at 48-weeks and 96-weeks of DTG/3TC, respectively, by combining the results of 11 real-world studies [ 72 ]. In fact, all the real-life studies available today, including the most recent, report on the excellent and sustained efficacy of this 2DR when used as a switch regimen ( Table 5 ) [ 15 , 23 , 62 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. These results are consistently maintained in both patients with a previous history of VF and resistance [ 23 , 62 , 74 , 75 , 76 , 80 , 82 ], and over longer observation periods [ 75 , 76 , 84 ].…”
Section: Diagnostic Framework For Dolutegravir Plus Lamivudine Two-drug Regimens In Virologically Suppressed Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Simplifying initial three drug antiretroviral drug regimens to two drug regimens has been documented to maintain viral suppression in individuals without prior virological failure or evidence of drug resistance [35•, 47]. Recent studies have reported that patients who had the M184I/V viral mutation before viral suppression can be successfully switched to a two drug regimen including lamivudine [48,49]. It should be noted that all these studies are on maintenance therapy; i.e., patients who were already virologically suppressed with combination antiretroviral drug therapy consisting of at least three different antiretroviral drugs were switched to dual therapy.…”
Section: M184i/vmentioning
confidence: 99%